2014
DOI: 10.4067/s0717-95022014000400043
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Developmental Anatomy of Testes and Epididymis of Gaddi Goats

Abstract: SUMMARY:The study revealed that the testes of one-day-old Gaddi goats have descended in the scrotum along with adnexa. They were elongated compressed latero-medially and became ovoid during their postnatal growth and morphogenesis. The two testes were not different significantly in their weight and measurement. The average weight which was about 2.9 gm at birth grew to 107 gm (40X) in pubertal animals and nearly maintained it during the post-puberty (113 g). The mean length (1.46 cm), width (0.85 cm) and thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, testicular weight did not alter significantly from birth (day 0) to 1 month of age ( p > 0.05), but from 2 months until puberty (6 months), it greatly increased ( p < 0.05). The biometrical results of the current investigation are congruent with those of earlier studies (in Yiling goats by Bo et al [ 14 ]; in Gaddi goats by Pathak et al [ 13 ]) in goats. The findings of the current investigation concur with those of Sadi and Gofur [ 16 ] in indigenous sheep and Gofur et al [ 17 ] in indigenous bulls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, testicular weight did not alter significantly from birth (day 0) to 1 month of age ( p > 0.05), but from 2 months until puberty (6 months), it greatly increased ( p < 0.05). The biometrical results of the current investigation are congruent with those of earlier studies (in Yiling goats by Bo et al [ 14 ]; in Gaddi goats by Pathak et al [ 13 ]) in goats. The findings of the current investigation concur with those of Sadi and Gofur [ 16 ] in indigenous sheep and Gofur et al [ 17 ] in indigenous bulls.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, it has been claimed that testicular size or weight is a reliable predictor of sperm production in the present and the future in a variety of animal species [ 2 ]. With increasing age, the biometrical values of the Black Bengal goat testis in the current study greatly increased, which supports previous observations [ 12 , 13 ] in different documented goat breeds. We observed that the testis development of the Black Bengal goat was slower in the early postnatal phase and quicker between 4 and 6 months of age, around the time when spermatogenesis starts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to Adebayo et al (2010), epididymis is an epithelial tube consisting of five segments, namely: the initial segment, head, corpus, cauda, and vas deferens. Epididymis serve as a source of nutrients for sperm maturation (Pathak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%